Respecting One's Elders: In Search of an Ontological Explanation for the Asymmetry Between the Proper Treatment of Dependent Adults and Children. - Anton, Audrey L. (Philosophical Papers, 2012)
The infantilization of older adults seems morally deplorable whereas very young children are appropriate recipients of such treatment. Children, we argue, are not mentally capable of acting autonomously and reasoning clearly. However, we have difficulty reconciling this justification with the fact that many of the elders whom we respect are mentally deficient in those very same ways. In this paper, I try to make sense of this asymmetry between our justifications for infantilizing the young and our conviction that our elders ought to be respected. I argue that our intuitions against adult infantilization are non-consequentialist (i.e., deontic). I consider several candidates for the deontic factor that might explain the asymmetry of our judgments and practices. I argue that a very specific kind of dignity (one that is socially constructed and reified) grounds our disparate judgments and treatments of very young and very old persons with similar needs.